Risks of climate change for food security in Central America and the Dominican Republic - Ulate Chacón, Enrique (2025)
This research addresses the risks that climate change represents for food security in Central America. The functioning of community law and regional institutions, and the normative   Revista de Ciencias Jurídicas-Edición Especial-Bioderecho(1-21) acts adopted from them, as well as some methodological proposals and final reflections, are explained. Within each of the eight SICA countries, agricultural policies and substantive regulations are established, which seek to promote not only the recognition of the risks of climate change for the food and nutritional security of Central America, but also to demonstrate the existence of methodological proposals and ongoing projects to address them.